Healing Response of Rat pulp Treated with an Injectable Keratin Hydrogel. Issue 3 (2017) - Ajay Sharma, Lavanya; Love, Robert M.; Ali, Mohammad A.; Sharma, Ajay; Macari, Soraia; Avadhani, Avadhoot; Dias, George J.
Background: Keratin has shown promising outcomes as a biomaterial due to its inherent bioactivity, biocompatibility and regenerative effects. The effect of keratin on repair and regeneration of dental tissues has never been studied before. Current therapies to treat pulp tissues involve its replacement with inert, synthetic materials that do not have a proper biological function, leading to failure and tooth loss. This study aimed to develop a biocompatible keratin hydrogel (KH) suitable for pulp therapies. Methods: Keratins extracted from sheep wool were isolated, quantified and reconstituted to form KH. Different concentrations of keratin gel suitable for dental application were characterized by rheological analysis. The optimized gel based on flow characteristics was studied further for microstructure including porosity, percentage swelling ratio and contact angle measurements, using analytical tools such as scanning electron microscopy (SEM), micro-computed tomography and goniometer. To assess both biocompatibility and pulpal response, KH was implanted into rat upper molar teeth following partial pulpotomy. After 28 days, the tissue sections were analyzed by histological and immunohistochemical methods to identify dentin matrix protein 1 (DMP-1) formation and compared with control (Ca(OH)2 -treated) teeth. Results: The results of the study demonstrated a viscous and injectable, porous, dimensionally stable, hydrophilic and biocompatible gel that allowed pulp healing to occur by a reparative response, with widespread DMP-1 expression. Conclusions: The findings of this study indicate that keratins can be developed as a biomaterial source for alternate biological treatment options for pulp therapies.